Long term photoacclimation responses of the coral Stylophora pistillata to reciprocal deep to shallow transplantation: photosynthesis and calcification - Cohen, Itay; Dubinsky, Zvy (Frontiers in Marine Science, 2015)
Reciprocal transplantation of Stylophora pistillata coral fragments between deep (30m) and shallow sites (3m) was conducted gradually and resulted with 100% survival. Photoacclimation of transplants at both depths showed two distinct phases: at the first phase, within two weeks, zooxanthellae density decreased below (at 3m) and increased beyond (at 30m) these of the control values at the new depth, while chlorophyll a per zooxanthellae cell remained as in the original depths, thereby fully adjusting areal chlorophyll concentration. On the second phase, after six months, zooxanthellae chlorophyll and their quantum yield (Fv/Fm) were adjusted at both new depths. Such regulated acclimation was also observed in the maximal photosynthesis rate of both transplants, whereas respiration adjustment was rapid. These results differ from previously reported rapid shade and light acclimation strategies hence we suggest that acclimation mechanism changes when certain symbiont type is exposed to depth out of its boundary zone. Despite seemingly having become physiologically acclimated, calcification at both new depths was only half the rate achieved by the controls, suggesting that the coral host requires even longer time than the symbionts to acclimate.